Stereotactic ablative radiotherapy for operable stage I non-small cell lung cancer: not ready for prime time - Connolly, James G.; Jones, Gregory D.; Caso, Raul; Jones, David R. (Annals of Translational Medicine, 2019)
Stereotactic ablative radiotherapy (SABR) is a wellaccepted treatment modality for patients with early-stage non-small cell lung cancer (NSCLC) who are thought to be inoperable or who decide not to undergo surgery (1). Some groups have recently suggested that SABR is a noninferior treatment approach for patients with operable stage I NSCLC (2,3). Surprisingly, there are no available data demonstrating the effectiveness of SABR at achieving pathologic complete response (pCR) in patients with NSCLC, a highly relevant point for all patients and perhaps particularly so for those who are candidates for surgery.